Cooperative Medical Insurance and the Cost of Care in Shandong, PR China: Perspectives of Patients and Community Members. (March 2015) - Mahmood, Mohammad Afzal; Raulli, Alexandra; Yan, Wang; Dong, Han; Aiguo, Zhang; Ping, Dong
This research was conducted to identify the cost of care associated with utilization of village clinics and membership of the New Cooperative Medical Scheme (NCMS) in 2 counties of Shandong province, PR China. A total of 397 community members and 297 patients who used the village clinics were interviewed. The average cost for primary care treatment of 1 episode of illness was about 55 yuan (about US$8). Although more than 50% of people had NCMS membership, many consider the monetary reimbursements as insufficient. The low insurance reimbursement rates and inability to pay out-of-pocket expenses compromise access to care. Delays can cause more serious illnesses with potential to overburden the secondary care at the township and county hospitals. Those rural people who have not yet enjoyed the benefits of China's economic development may not benefit from recent health care reform and finance mechanisms unless schemes such as the NCMS provide more substantial subsidies.